FAMILY SUBJECTIVE WELL-BEING AT THE EARLY OF COVID-19 PANDEMIC IN INDONESIA - Oktriyanto Oktriyanto; Sri Lilestina Nasution; Resti Pujihasvuty; Mardiana Dwi Puspitasari; Hilma Amrullah; Chairunnisa Murniati; Herien Puspitawati; Tin Herawati (Universitas Airlangga, 2023)
Families in Indonesia experienced changes and economic pressures in the early days of the COVID-19 pandemic. This research is very important to know the full picture of family resilience in Indonesia, especially in the economic aspect. This study analyzes economic changes, coping strategies, and their effects on subjective family welfare at the pandemic's start. Data were collected through a Family Condition Survey, carried out specifically through online media, for 14 days in 34 provinces. The unit of analysis in this study is the family, that is married couples who have or do not have children, with a total sample of 20,680 respondents. This study conducted univariate, bivariate, and multivariate analyses using Cross Tabulation, Chi-Square Test and Binary Logistic Regression with Odds Ratio. The results of the study show that there are worsening economic changes, such as working conditions, finances and food adequacy. In this case, environmental factors are the family's socioeconomic and financial conditions (education, income, employment), which are still the main factors and significantly influence the subjective well-being of the family. However, the subjective welfare of families in Indonesia is still quite good; most families are still happy, remain grateful, and communicate well. Coping strategies in managing family finances, such as saving and using savings, are the most widely used. However, these efforts are constrained by low family income and increased additional needs during the pandemic. There is a need for further research that can fully describe post-pandemic family economic coping strategies in the last 12 months.